An Investigation of High-Achieving African-American Students Attending Community Colleges: A Mixed Methods Research Study. Issue 4 (3rd April 2018) - Gipson, John; Mitchell, Donald; McLean, Carolyn
ABSTRACT: While much more research has been conducted about African-American college students in recent decades, there still exists a need for further explorations concerning factors related to student success and retention. For example, articles often explore the experiences of African-American students at four-year institutions and often use deficit frameworks instead of focusing on the experiences of successful students. To add to what is known, this article summarizes the findings of a multi-institutional mixed methods research study that explored the experiences of high-achieving African-American students attending community colleges. Specifically, the researchers explored noncognitive factors that influenced high academic achievement—defined as grade point average (GPA) higher than 3.00, why students considered leaving an institution, and why students decided to remain enrolled. Findings suggested that studying alone promoted a high cumulative GPA and increased the likelihood students never seriously considered leaving their institution. Studying alone, family relationships, hours spent studying with family, engaged and supportive faculty, financial aid, and the strive to succeed also promoted persistence. Relating to sex differences, student organizational involvement appeared to be more important for male persistence than female persistence at a significant level. The article closes with implications for future research and practice.